Does the stock market cause economic growth? Portuguese evidence of economic regime change - Marques, Luís Miguel (2019)
The relationship between stock market and economic growth is tested for Portugal (1993–2011), which is a small open economy dependent on bank financing. The relationship between economic growth and bank financing is also appraised. Using Vector Autoregressive (VAR) modeling, Granger causality, variance decomposition and impulse response function are discussed. The physical replacement of the currency, as a consequence of the integration in the European Monetary Union, proves to be an economic regime change. The effect of the subprime crisis was also proved. There is evidence of Granger bidirectional causality between the stock market and economic growth. Meanwhile, there was no evidence of causality running from bank financing to economic growth.